Influence of elastic strains on the mask ratio in glassy polymer nanoimprint - CROSS, GRAHAM; O'CONNELL, BARRY SEAMUS; PETHICA, JOHN BERNARD (American Institute of Physics, 2005)
During glassy polymer nanoimprint, a supported film is extruded from protruding spunchd to recessed scavityd regions of a patterned stamp. The completeness of this extrusion determines the mask ratio for lithographic applications. We show that, for a given punch contact size, there is a residual layer of unextruded material with a mean thickness that is independent of initial film thickness, stamping time, or applied maximum load. Depth sensing indentation enables us to monitor deformation during the imprinting as well as after, and so understand the deformation process involved. It is found that both the geometry and mean thickness of the residual layer are influenced by the overall elastic properties of the stamping system.
PUBLISHED
Keywords: polymer films; nanolithography; soft lithography; masks; indentation; internal stresses; elasticity; plastic deformation